Anna Zelenay. Twarz poetki - Maliszewski, Karol (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article presents the life and work of Anna Zelenay, a forgotten poetess from Kłodzko. The author shows the impact of her disease on awareness and shape of her poems written often in hospitals and sanatoriums. He discusses the critics on her poetry and the poetess’s place in her own time and generation. The author indicates that the existence of Zelenay on the literary scene is related to the activities of Literary Club of Kłodzko, and bigger promotion of her work is caused with her active participation in a very important literary event of the sixties, in Poetic Springs of Kłodzko.